Front Cover: Effect of gem‐Difluorination on the Key Physicochemical Properties Relevant to Medicinal Chemistry: The Case of Functionalized Cycloalkanes (Chem. Eur. J. 19/2022). Issue 19 (11th March 2022) - Holovach, Sergey; Melnykov, Kostiantyn P.; Skreminskiy, Artem; Herasymchuk, Maksym; Tavlui, Olha; Aloshyn, Danylo; Borysko, Petro; Rozhenko, Alexander B.; Ryabukhin, Sergey V.; Volochnyuk, Dmitriy M.; Grygorenko, Oleksandr O.
Abstract : The CF2 dragon reborn ! The difluoromethylene dragon has evolved from difluorocyclopropanations (presented in a series of previous covers, see Adv. Synth. Catal ., DOI: 201801304 and Eur. J. Org. Chem . 201900911 ) to the full strength of all other gem ‐difluorocycloalkanes. In the Research Article by O. O. Grygorenko and co‐authors (DOI: 10.1002/chem.202200331 ), the key in vitro properties of functionalized gem ‐difluorinated cycloalkanes (p K a, log P, aqueous solubility, and intrinsic clearance) are discussed thoroughly.